Income related inequalities in avoidable mortality in Norway: A population-based study using data from 1994–2011. Issue 7 (July 2015) - Kinge, Jonas Minet; Vallejo-Torres, Laura; Morris, Stephen
Highlights: Avoidable, amenable and preventable deaths in Norway have declined between 1994 and 2011. There were socioeconomic inequalities in avoidable, amenable and preventable deaths. The socioeconomic inequalities in such deaths remained stable between 1994 and 2011. Socioeconomic inequalities in avoidable deaths did not correlate with variations in the Gini index of income inequality. Abstract: Objective: The aim of this study was to measure income-related inequalities in avoidable, amenable and preventable mortality in Norway over the period 1994–2011. Methods: We undertook a register-based population study of Norwegian residents aged 18–65 years between 1994 and 2011, using data from the Norwegian Income Register and the Cause of Death Registry. Concentration indices were used to measure income-related inequalities in avoidable, amenable and preventable mortality for each year. We compared the trend in income-related inequality in avoidable mortality with the trend in income inequality, measured by the Gini coefficient for income. Results: Avoidable, amenable and preventable deaths in Norway have declined over time. There were persistent pro-poor socioeconomic inequalities in avoidable, amenable and preventable mortality, and the degree of inequality was larger in preventable mortality than in amenable mortality throughout the period. The income-avoidable mortality association was positively correlated with income inequalities in avoidable mortality over time. There was little or no relationship between variations in the Gini coefficient due to tax reforms and socioeconomic inequalities in avoidable mortality. Conclusions: Income-related inequalities in avoidable, amenable and preventable mortality have remained relatively constant between 1994 and 2011 in Norway. They were mainly correlated with the relationship between income and avoidable mortality rather than with variations in the Gini coefficient of income inequality.